DEMAND FOR AGRITOURISM IN SRI LANKA - MALKANTHI S H P (ASEAN Journal on Hospitality and Tourism, 2013)
This study has examined the factors affecting for the demand for agritourism in Sri Lanka. Demographic factors, awareness and desire on agritourism of the visitors and purposes of visiting agritourism operations have also been examined. The study was based on a survey of 128 local visitors in one of the agritourism operations in the country. Stepwise regression analysis was used to analyze the data. Agritourism visitors are middle aged educated employees having higher monthly income. Further most of them are married and have children. The awareness level on agritourism in Sri Lankan visitors is at a lower level. Agritourism visitors have mentioned four main purposes of visiting agritourism operations such as resting, enjoyment and recreation, education. Results of the regression analysis shows that only three variables (household income, urban residency, and availability of vehicle facility) have positive effects and two variables (the distance to the agritourism destination and individual travel cost) have negative effects for the demand for agritourism in Sri Lanka.